THE EFFECT OF Spirulina platensis FLUOR SUPPLEMENTATION TO ARTIFICIAL FEED ON INCREASING OF GOLDFISH (Carassius auratus) COLOR QUALITY - fitriyani gumilarsah; mulyana mulyana; fia sri mumpuni (Universitas Djuanda, 2019)
The experimental research was carried out on October 2018 at The Fisheries Laboratory, Djuanda University, Bogor. The research is aimed to know the effect of Spirulina platensis fluor supplementation to artificial feed on increasing of goldfish color quality. The experimental research used completely randomized design with 4 treatments and each 3 replications. The treatments are A (Control), B (the supplementation of Spirulina platensis fluor with a dose of 3 %/1 kg of artificial feed), C (the supplementation of Spirulina platensis fluor with a dose of 6 %/1 kg of artificial feed), dan D (the supplementation of Spirulina platensis fluor with a dose of 9 %/1 kg of artificial feed). The increasing of color quality and the survival rate of goldfish has been evaluated. The results of research showed that the fish color changes on the thirteenth day began to look thick and bright. The best dose is obtained in treatmens C and D. The survival rate of 100 % in all treatments. Key words : Color quality, Goldfish, Spirulina platensis, survival rate